Estimations of energy of noncovalent bonding from integrals over interatomic zero‐flux surfaces: Correlation trends and beyond. Issue 21 (27th April 2018) - Romanova, Anna; Lyssenko, Konstantin; Ananyev, Ivan
Abstract : Bonding energies of 50 associates composed by neutral molecules (atoms) and bounded by various weak noncovalent interactions are calculated within the DFT framework using the PBE0/aug‐cc‐pVTZ combination. The electronic virial and electron density values at bond critical points together with their integrals over interatomic surfaces are tested to check their ability to estimate bonding energies. Two correlations schemes dealing with integrals over interatomic surface are suggested to estimate bonding energy of any noncovalent interaction. The physical meaning of explored and several known correlations is discussed. Methods to estimate interatomic surface integrals of electronic virial and electron density are proposed. © 2018 Wiley Periodicals, Inc. Abstract : Two methods to estimate energy of any weak noncovalent interaction ( E B ) are proposed basing on integrals over interatomic surfaces. Relations between these integrals and quantities at bond critical points are found.